Volume 6: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-27725
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Tip Clearance Flow at Near-Stall Condition in a Transonic Axial Compressor Rotor

Abstract: It is known that the tip clearance flow is dominant and very important flow phenomena in axial compressor aerodynamics because the tip clearance flow has a great influence on the stability as well as aerodynamic loss of compressors. Our goal is to clarify the behavior of tip clearance flow at near-stall condition in a transonic axial compressor rotor (NASA Rotor 37). In the present work, steady and unsteady RANS simulations were performed to investigate vortical flow structures and separated flow field near th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…is adequate to represent the main phenomena characterizing the near stall conditions, a preliminary analysis was performed for a geometry presenting a similar behavior to the compressor in study. For a transonic unshrouded compressor with axial inlet and pronounced tip gap in fact, the onset of unsteady disturbances at low mass flow is likely to be generated at the leading edge of the inducer, by the breakdown of the tip leakage vortex interacting with the passage shock [22]. In some circumstances, this leads to a local increase of blockage, which rotates within the annulus [7,8].…”
Section: Validation Of the Numerical Approach: The Nasa Rotor 37mentioning
confidence: 98%
“…is adequate to represent the main phenomena characterizing the near stall conditions, a preliminary analysis was performed for a geometry presenting a similar behavior to the compressor in study. For a transonic unshrouded compressor with axial inlet and pronounced tip gap in fact, the onset of unsteady disturbances at low mass flow is likely to be generated at the leading edge of the inducer, by the breakdown of the tip leakage vortex interacting with the passage shock [22]. In some circumstances, this leads to a local increase of blockage, which rotates within the annulus [7,8].…”
Section: Validation Of the Numerical Approach: The Nasa Rotor 37mentioning
confidence: 98%
“…It rolls-up into a tip leakage vortex that disturbs the main flow, especially at highly loaded operating points. Indeed, several experimental and numerical studies have shown that the tip leakage vortex interacts with the endwall boundary layer and the shock wave in the passage [1,2,3] . The abrupt change of the core vortex downstream the shock wave somewhat corresponds to a "vortex breakdown" which blocks the passage flow near the tip gap region.…”
Section: Introductionmentioning
confidence: 99%
“…They also proposed that tip leakage vortex breakdown as a possible cause of stall inception in a transonic compressor rotor. Yamada [7][8] numerically examined that the tip leakage vortex breakdown occurred near-stall condition in a transonic compressor. This vortex breakdown resulted in the rotating disturbance.…”
Section: Introductionmentioning
confidence: 99%